Measurement of donor‐specific HLA antibodies following plasma exchange therapy predicts clinical outcome in pediatric heart and lung transplant recipients with antibody‐mediated rejection. Issue 4 (21st February 2013) - Jackups, Ronald; Canter, Charles; Sweet, Stuart C.; Mohanakumar, T.; Morris, Gerald P
<x xml:space="preserve">Abstract</x> Therapeutic plasma exchange (TPE) is an increasingly utilized immunosuppressive adjunct for treatment of antibody‐mediated rejection (AMR) following organ transplantation. TPE works through removal of donor‐specific HLA antibodies (DSAs) in the recipient's plasma. However, there is no clear laboratory measure evaluating efficacy of removal of DSAs or predicting clinical outcome. We hypothesized that semi‐quantitative DSA measurement by multiplex HLA antibody immunoassay may provide qualitative and quantitative data for DSA clearance and predict treatment efficacy. To evaluate this, we retrospectively investigated DSA concentrations and clinical outcome for 21 pediatric patients who received 31 cycles of TPE peri‐operatively as an adjunct treatment for transplantation in the setting of a positive cytotoxic crossmatch (CXM) and in recipients with AMR following heart or lung transplantation. Immunoassay measurement of DSAs during 15/20 cycles correlated significantly with clinical outcome in the AMR treatment group (P = 0.02), demonstrating the utility of DSA measurement in predicting clinical outcome. In contrast, immunoassay correlated with clinical outcome in only 7/11 patients treated peri‐operatively with TPE for CXM‐positive transplantations (P = 0.58). Changes in mean fluorescence intensity (MFI) for the DSAs correlated better with clinical response than surrogate CXM titers in a subset of patients. We conclude that semi‐quantitative measurement of DSAs by immunoassay can predict clinical response to TPE for treatment of AMR is more reliable than surrogate CXM titer, and should be used to guide TPE treatment of AMR. J. Clin. Apheresis 28:301–308, 2013. © 2013 Wiley Periodicals, Inc.